Effects of 5-HT2C receptor modulation and the NA reuptake inhibitor atomoxetine in tests of compulsive and impulsive behaviour. (15th June 2020) - Higgins, Guy A.; Brown, Matt; St John, Jessica; MacMillan, Cam; Silenieks, Leo B.; Thevarkunnel, Sandy
Abstract: Drug repositioning has gained strategic value as a reaction to high attrition rates of new drugs as they pass through the clinical development process. The 5-HT2C receptor agonist lorcaserin (Belviq®), and the selective NA reuptake inhibitor atomoxetine (Strattera®) represent two drugs FDA approved for obesity and ADHD respectively. Although both drugs are of differing pharmacological class, each share a property of regulating impulsive behaviours in preclinical studies, and thus represent candidates for consideration in clinical conditions labelled as 'impulsive-compulsive disorders'. The present studies investigated both drugs, as well as the highly selective 5-HT2C agonist CP-809101 in two tests of compulsive action: schedule-induced polydipsia (SIP) and increased perseverative [PSV] (and premature [PREM]) responses emitted during an extended ITI 5-choice task. While lorcaserin (0.06–0.6 mg/kg), CP-809101 (0.1–1 mg/kg) and atomoxetine (0.1–1 mg/kg) each reduced both PREM and PSV measures in the 5-choice task, at equivalent doses only lorcaserin and CP-809101 affected excessive water intake in the SIP task, atomoxetine (0.1–2 mg/kg) was essentially ineffective. Further evidence supporting a role of the 5-HT2C receptor as an important regulator of impulsive-compulsive behaviours, the selective antagonist SB-242084 produced the opposing effects to lorcaserin, i.e promoting both impulsive and compulsive behaviours. The profile of atomoxetine may suggest differences in the nature of compulsive action measured either as non-regulatory drinking in the SIP task, and PSV responses made in a 5-choice task. These studies support the consideration of 5-HT2C receptor agonists, typified by lorcaserin, and atomoxetine as potential treatments for clinical conditions categorised as 'impulsive-compulsive disorders'. This article is part of the special issue entitled 'Serotonin Research: Crossing Scales and Boundaries'. Highlights: Lorcaserin (5-HT2C agonist) and atomoxetine examined on measures of impulsivity and compulsivity. Lorcaserin reduced both measures, particularly in extreme (high) phenotype subjects. SB-242084 (5-HT2C antagonist) increased impulsive and compulsive measures. Atomoxetine reduced impulsivity, but had differential effects against compulsive behaviour. Implications for 5-HT2C agonists and atomoxetine as treatments for impulsive-compulsive disorders.